2015
DOI: 10.1111/sdi.12440
|View full text |Cite
|
Sign up to set email alerts
|

C‐reactive Protein: Repeated Measurements will Improve Dialysis Patient Care

Abstract: Systemic inflammation is a common feature in the uremic phenotype and associates with poor outcomes. The awareness regarding the importance of inflammation assessment in chronic kidney disease (CKD) patients has risen in recent years, and despite the development of novel biomarkers, C-reactive protein (CRP) is still the most measured inflammatory parameter. Notwithstanding, the possible weak points of CRP determination, this biomarker has demonstrated being useful both for guidance in clinical practice and for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
32
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 109 publications
(90 reference statements)
1
32
1
Order By: Relevance
“…Most of the studies demonstrated the association among malnutrition, inflammation, and atherosclerosis syndromes cross‐sectionally because CRP measurements were not repeated regularly . We assessed CRP and components of MIA syndrome annually in CKD subjects as per some authors’ recommendation . In subjects with CKD, we demonstrated that the high baseline serum B2M was associated with death, death or dialysis, and CVEs, as well as the occurrence of MIA syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the studies demonstrated the association among malnutrition, inflammation, and atherosclerosis syndromes cross‐sectionally because CRP measurements were not repeated regularly . We assessed CRP and components of MIA syndrome annually in CKD subjects as per some authors’ recommendation . In subjects with CKD, we demonstrated that the high baseline serum B2M was associated with death, death or dialysis, and CVEs, as well as the occurrence of MIA syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Persistent inflammation, usually assessed by C‐reactive protein (CRP) levels, is a characteristic feature in advanced chronic kidney disease (CKD). It is caused by multiple factors linked to the toxic uremic milieu, senescence and even the dialysis technique itself . Persistent inflammation contributes to decreased S‐Alb levels, promotes a prematurely aged phenotype, and plays a central role in the Malnutrition, Inflammation and Atherosclerosis (MIA) syndrome, which predicts poor clinical outcomes .…”
mentioning
confidence: 99%
“…Persistent inflammation contributes to decreased S‐Alb levels, promotes a prematurely aged phenotype, and plays a central role in the Malnutrition, Inflammation and Atherosclerosis (MIA) syndrome, which predicts poor clinical outcomes . Because there is no consensus regarding the appropriate cutoff concentration for CRP in CKD, it has been problematic to ascertain and understand the magnitude, variability, and consequences of uremic inflammation . Moreover, according to the inflammation‐catalyst hypothesis, persistent inflammation modifies the risk factor profile and exacerbates the effects of a range of prevalent risk factors in CKD .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Actually, it was recently recommended to monitor inflammation through the evaluation of inflammatory markers in CKD patients, since persistent inflammation may be a silent reflection of pathophysiologic disturbances [33]. CRP seems to be the most useful biomarker in clinical practice for guidance of inflammation and to estimate risk in CKD patients [33].…”
Section: Anemia and Inflammationmentioning
confidence: 99%